2018
DOI: 10.1115/1.4040161
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Mode Coupling Chatter Detection and Suppression in Robotic Milling

Abstract: A new method for online chatter detection and suppression in robotic milling is presented. To compute the chatter stability of robotic milling along a curvilinear tool path characterized by significant variation in robot arm configuration and cutting conditions, the tool path is partitioned into small sections such that the dynamic stability characteristics of the robot can be assumed to be constant within each section. A methodology to determine the appropriate section length is proposed. The instantaneous cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The author established a 2DOF dynamic model of the robotic arm milling process by simplifying the cutting force, and obtained the stability criterion in the machining plane by using BIBO stability criterion. Cen et al (Cen et al, 2018; investigated the effect of cutting force on the mode coupling chatter of robotic arm milling, and improved the criterion proposed by Pan et al via introducing the conservative matrix transformation to optimize the feed rate. Mousavi et al (2018) focused on the dynamic model-based predictions of stable and unstable zones along a robotic machining trajectory with one degree of functional redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…The author established a 2DOF dynamic model of the robotic arm milling process by simplifying the cutting force, and obtained the stability criterion in the machining plane by using BIBO stability criterion. Cen et al (Cen et al, 2018; investigated the effect of cutting force on the mode coupling chatter of robotic arm milling, and improved the criterion proposed by Pan et al via introducing the conservative matrix transformation to optimize the feed rate. Mousavi et al (2018) focused on the dynamic model-based predictions of stable and unstable zones along a robotic machining trajectory with one degree of functional redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…They subsequently developed a stability chart that can be used to select chatter-free spindle speeds when machining aluminum. In their robotic milling experiments on a KUKA KR210 IR, Cen et al [23] also found that chatter instability occurs more readily when milling in one Cartesian coordinate direction compared to milling in a direction orthogonal to it. Mousavi et al [24] have also shown that the natural frequencies of a serial-link robot can vary significantly along a tool path due to a continuously changing robot configuration.…”
Section: Robot Stiffnessmentioning
confidence: 99%
“…However, the research on robotic milling technology has mainly focused on improving the robotic machining accuracy and the vibration suppression during the milling process, and the research and comprehensive analysis on the influence of milling parameters on milling load, surface quality and vibration during robotic milling are insufficient. Therefore, it is necessary to study the effects of process parameters on robotic milling performance [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%